Charge‐Induced Shifts in Chiral Surface Plasmon Modes in Gold Nanorod Assemblies. (7th December 2018) - Kumar, Jatish; López‐Martínez, Elena; Cortajarena, Aitziber L.; Solís, Diego M.; Taboada, José M.; Díez‐Buitrago, Beatriz; Pavlov, Valeri; Liz‐Marzán, Luis M.
Abstract: A detailed investigation of the effect of electron injection on the chiral plasmon modes of helical nanorod assemblies is presented. An increased surface plasmon frequency of the electron gas due to the addition of electrons leads to a blue‐shift in the corresponding chiral surface plasmon modes. The mechanism behind the shift in plasmonic chirality due to nanorod charging is investigated using theoretical simulations. Charging of the nanorods alters the surface electron density, thereby modifying the plasma frequency and causing a change in the dielectric function. The nature of the plasmon shift and the intensity of chiral surface plasmons are found to be largely dependent on the extent of electron addition. At extended periods of time, the blue shifted band slowly shifts back toward the red, due to transfer of electrons back to the medium, leading to discharging of the nanorods. Abstract : Upon addition of a strong reducing agent to a dispersion of gold nanorods adsorbed on amyloid fibers, both localized surface plasmon and circular dichroism bands are blue‐shifted. Electron microscopy and numerical simulations confirm that the observed spectral shifts are due to an increase in electron density in the nanorods. This effect opens up new opportunities to tune the frequency of chiral plasmon modes.